Study on the effect of film thickness on the conversion efficiency of the tandem solar cell using Silvaco TCAD / Abd Farid Mohd Asannan - Mohd Asannan, Abd Farid (2009)
Analysis on the effect of film thickness on the conversion efficiency of the tandem solar cell using Silvaco TCAD was conducted in this paper. Several parameters such as thickness, short circuit current (Isc), open circuit voltage (Voc) were investigated and the ATHENA/ATLAS profile for tandem solar cell structure was develop to help understanding the effect of thickness of the tandem solar cell on its conversion efficiency (%). 2 samples of tandem solar cell were developed in this paper which includes fully crystalline silicon (Si) tandem solar cell and combination of crystalline silicon solar cell with gallium arsenide (GaAs). The cutline to extract the net doping of tandem solar cell in TONY PLOT with photogeneration current was done for investigating the dependence of the thickness to the conversion efficiency. From both samples, 3 parameters were varies which is (1) thickness, (2) ion implantation energy and (3) dose concentration. Each of the experiments were obtained 10 readings of Isc and Voc. Then, the values of efficiency were calculated using conversion efficiency solar cell formula. All simulation was done by using SILVACO TCAD.